Does ideology influence the ambition level of climate and renewable energy policy? Insights from four European countries. Issue 1 (2nd January 2021) - Thonig, Richard; Del Río, Pablo; Kiefer, Christoph; Lázaro Touza, Lara; Escribano, Gonzalo; Lechón, Yolanda; Späth, Leonhard; Wolf, Ingo; Lilliestam, Johan
ABSTRACT: We investigate whether political ideology has an observable effect on decarbonization ambition, renewable power aims, and preferences for power system balancing technologies in four European countries. Based on the Energy Logics framework, we identify ideologically different transition strategies (state-centered, market-centered, grassroots-centered) contained in government policies and opposition party programs valid in 2019. We compare these policies and programs with citizen poll data. We find that ideology has a small effect: governments and political parties across the spectrum have similar, and relatively ambitious, decarbonization and renewables targets. This mirrors citizens' strong support for ambitious action regardless of their ideological self-description. However, whereas political positions on phasing out fossil fuel power are clear across the policy space, positions on phasing in new flexibility options to balance intermittent renewables are vague or non-existent. As parties and citizens agree on strong climate and renewable power aims, the policy ambition is likely to remain high, even if governments change.